Injury prevention knowledge and practices of high school wrestling athletes in the school division of Tuguegarao City - Adduru, Pamela Gem Q. 2000-
With the escalating incidence of sports-related injuries, particularly in contact sports like wrestling, the research addresses the critical need for an enhanced understanding of injury prevention and management strategies. This study investigated the injury prevention knowledge and practices among high school wrestling athletes in the Schools Division of Tuguegarao City, Philippines. A qualitative case study using an inductive approach, employing survey through Google form and online focus group discussion using Google Meet and semi-structured interviews with high school wrestling athletes was utilized. Thematic analysis was used to code, develop, and refine themes. The study aimed to describe and understand the knowledge and practices related to the prevention of sports injuries among high school wrestling athletes in the Division of Tuguegarao City. The themes that emerged are experiential knowledge and awareness, actual strategies on injury prevention, and management and recovery practices. The participants’ experiential knowledge and understanding on injury prevention revolved on common injuries, sports’ demands and importance. However, their knowledge and understanding are not enough for them to prevent injuries during training and competitions. Moreover, the athletes’ actual strategies for injury prevention include training practices, warm-up routines, wearing protective gears, self-awareness, and education. Finally, immediate first aid measures, such as rest, cold compress application, and hilot were commonly used by the athletes